Concept and Conception of Civil Society in Western and Islamic Traditions: A Comparative Analysis of Secular and Islamic Faith-based Civil Society Practitioners in Pakistan and Bangladesh - Karim Sajjad Sheikh; Khalil Ahmad; Ayesha Farooq; Fauzia Saleem Alvi (Journal of Political Studies, 2017)
The present paper attempts to explore diversity of the concept of civil society in the Western (secular) and Islamic (faith-based) traditions. This paper reviews and discusses the major ideas, which have informed historical and contemporary debates about civil society in the West and in the world of Islam. The present paper is part of first author’s PhD research project, “The Role of Civil-Society Organisations in Poverty Alleviation: A Comparative Study of Faith-Based and Secular Local, National and Global Organisations in Pakistan and Bangladesh”. The study is based on a combination of secondary sources and qualitative, face-to-face interviews with the representatives of secular and faith-based civic-society organisations in Pakistan and Bangladesh. The concept of civil society is embedded in diverse socio-political traditions of the Western and Islamic world. In Western and Islamic traditions there is diversity in the understanding of the concept of civil society; it has a variety of envisioned functions or roles, and alternative requirements for a wellfunctioning civil society. Both the Islamic and Western civil society ideas and practices promote the ‘good or well-being’ of people. However, Islamic faith- based civil society practitioners view well-being in terms of religious obligations with more focus upon spiritual happiness and salvation after death; while Western civil society traditions rest on enlightenment and modern intellectual traditions and individualism.